Simulation and prediction of groundwater pollution based on GMS: a case study in Beijing, China. Issue 1 (July 2021) - Zhao, Xiaoning; Wang, Daqing; Xu, Haoli; Ding, Zhibin; Shi, Yue; Lu, Zhao; Cheng, Zijian
Abstract: Groundwater is an important fresh water resource, which is very important for human survival. In this study, the hydrogeological information of the study area was obtained through field investigation and data reference, and the groundwater flow field in the study area was constructed using GMS (Groundwater Modeling Systems) software. The actual drilling water level data was used for verification. Based on the groundwater flow field, combined with pollution source sampling and testing data, a groundwater pollutant transport model was constructed, and the pollution situation was comprehensively evaluated. The results showed that once the landfill leachate and lead-acid battery plant waste liquid leaked in the study area, the groundwater in more than 40% of the study area will be greatly affected and it was not easy to recover. Therefore, predicting and simulating the transport of groundwater pollutants has a certain value, and can provide a scientific basis for preventing and controlling environmental degradation and protecting groundwater resources.